Kepulauan Riau Sebagai Daerah Perbatasan Dengan Masalah Kewarganegaraan Ganda Terbatas - Siska Sukmawaty (Jurnal Selat, 2016)
Citizenship is the issue relating to citizen, while naturalization is the procedures for foreigners to obtain Indonesian citizenship as mandated by law no 12 of 2006 concerning citizenship. Riau Archipelago Province as the border area had an impact on the number of international marriage consequences that affects the status of the child which born within the international marriage. Limited dual citizenship filing of applications filed at the Regional Office of the Ministry of Justice and Human Rights of Riau Archipelago Province the raises issues related to the governing law of citizenship and the filing procedure of it. Emerging issues related to the filing of citizenship in border regions associated Islands received a request for the limited dual citizenship and statutory provisions that set the date line of the submission on the limited dual citizenship and statutory provisions that set the date line of the submission on the limited dual citizenship until August 1, 2010 Keywords : Citizenship.